(untitled) - Misfeldt, Trevor (Cambridge, UK, 2004)
The book provides conventions for formatting, naming, documentation, programming, and packaging for the latest ANSI standard of C++, and also includes discussion of advanced topics such as templates.
Keywords: C++ (Computer program language),Ngôn ngữ lập trình máy tính